Effect of Welding Current on Weldments Properties in MIG and TIG Welding - Sh. Hasan, Aysha; M. Ali, Obed; M. Alsaffawi, Adnan (International Journal of Engineering and Technology, 2018)
Welding is an important process commonly used to join the different materials together. There are many methods for welding process;therefore, the specifications of weldments will depend on the type of welding process. In this study, investigation of the effect of electrical current on the weldment mechanical propertieswas conducted. Medium carbon steel & stainless steel were welded using two types of joints (single Lap joint and single v-groove Butt joint). The results showedthat the temperature increased with increasing the electrical current. A significant effect of electrical current on the ultimate tensile strength of the weldments is obtaineddepending on the joint type rather than welding type.Furthermore, there was a noticeable effect for the joining method on the heat generated.The heat generated increases with increasing the electrical current for all weldments (lap & butt) joint in both TIG & MIG welding process. However,the amount of heat generated was for TIG welding process specimens higher than from MIG welding process specimens for Butt and Lap type joints.Â